How to nudge industrial customers to accept free-to-fee service price switches? - Keränen, Joona; Salonen, Anna; Terho, Harri; Munnukka, Juha (Elsevier BV, 2026)
Capturing value from service provision is a persistent challenge for many firms. Sometimes, business-to-business (B2B) suppliers offer services for free to increase customer adoption at the early stages of servitization or to boost product sales. If customers initially receive services for free, managing the switch from free-to-fee at later stages is difficult. To address this managerial challenge, we examine how sellers of digital industrial services can use behavioral nudges to increase customer acceptance of a free-to-fee price switch. Using a scenario-based experiment with 386 industrial buyers, we test the effects of three choice architectures—motive justification, social influence-focused information provision, and loss versus gain framing—on customer willingness to switch. Our findings indicate that these nudges increase acceptance, but their effects range from small to medium and occur only among attentive audiences. The study contributes to both theory and practice by demonstrating that cognitive biases and decision-making heuristics play a role in B2B service pricing. Although nudges should not be viewed as a universal solution for behavioral change, their simplicity and low implementation costs make them a practical tool for managers. We encourage future research to critically examine the boundary conditions that influence nudge effectiveness across diverse B2B decision-making situations.